Broken business : seven steps to reform good companies gone bad - Hernandez, José R., 1974- (Gildan, 2019)
Broken Business: Seven Steps to Reform Good Companies Gone Bad is an essential book for leaders seeking a concise review at how things can go wrong, how to deal with scandal fallout, and how to ultimately become a better company.